Lung cancer invading the superior vena cava – surgical treatment. A short and up-to-date review - Nikolaidis, Eleftherios; Bolanos, Nikolaos; Anagnostopoulos, Dimitrios; Leivaditis, Vasileios; Grapatsas, Konstantinos; Koletsis, Efstratios; Papatriantafyllou, Athanasios; Panagiotopoulos, Ioannis; Mulita, Francesk; Baltayiannis, Nikolaos; Dahm, Manfred; Chatzimichalis, Antonios (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2023)
Lung cancer is one of the leading causes of cancer-related deaths worldwide. Superior vena cava syndrome (SVCS) is a rare but potentially life-threatening complication of lung cancer, occurring in approximately 5–10% of cases. There are difficulties in the process of surgical treatment of SVC infiltrated by lung tumors but the contribution of technological evolution and innovation is promising. At the same time, the amelioration of survival rates of patients subjected to surgical treatment is equally promising. The reported outcomes of surgical treatment for SVC invasion due to lung tumors vary depending on the extent of the tumor and the patient’s overall health status. However, studies clearly suggest that surgical treatment can improve survival and quality of life in selected patients. The literature review showed that the surgical approach to lung cancer invading the SVC constitutes the most indispensable treatment which helps to achieve the long-term survival of patients.